Compaction control of clay barriers by centrifugation. Issue 3 (September 2001) - Mitchell, R.J.; Knight, M.A.
Abstract : Although field compaction techniques and specifications for achieving a homogeneous clay barrier are well known, changes in borrow materials due to weathering or stratifications can lead to variability in the performance of such compacted barriers. Field density testing can give an indication of barrier quality but quality control should also incorporate hydraulic conductivity testing. Hydraulic conductivity testing on a daily basis is a difficult task. This paper outlines a methodology for barrier control testing by centrifugation and discusses why centrifuge testing is superior to bench testing with elevated gradients. The use of centrifugation for evaluating barrier diffusion and possible long-term change in hydraulic conductivity is also discussed.